Usefulness of the Khorana model in oncological patients with venous thromboembolic disease (Boletin Médico de Postgrado, 2020)
The goal of this study was to describe the utility of the Khorana model as a risk stratifier for venous thromboembolic disease (VTE) in oncological patients hospitalized in the Servicio de Medicina of the Hospital Central Universitario Dr. Antonio María Pineda during the period February-April 2018. 20 patients were evaluated. The results showed predominance of female sex (1:0.3) with an average age of 52.9 ± 13.1 years. Regarding the location of cancer, the highest percentage (30%) was gynecological followed by digestive (25%) and hematological (15%). According to the histological type of tumor, the highest percentage was carcinoma (82.3%). The distribution of patients according to the type of VTE was deep vein thrombosis in the left lower limb in 65% of cases and pulmonary thromboembolism in 20% of cases. According to the Khorana model, 55% of patients were stratified in the intermediate risk group and 45% in the high-risk group. The use of the Khorana model allowed stratification of most patients at intermediate risk and all within intermediate/high risk. The use of the Khorana model constitutes a useful and applicable tool in the risk stratification of VTE.
Keywords: cancer; Khorana model; venous trombosis